Study on Impacts of Energy Absorbing Devices on Train Collision Energy Absorption - Bin LIU; Shoune XIAO; Bing YANG; Tao ZHU; Guangwu YANG (机车电传动)
In order to study the effects of different configurations of force-displacement relationship of the additional energy absorbing device on the absorption of kinetic energy during a collision, a multi-rigid body dynamics model of two identical eight-car trains was established, calculated and analyzed. The results shows that under the premise of ensuring the same designed capacity, the design of force-displacement curve as multi-step with constant gradient or one which has a certain positive slope can make the device absorb more impact kinetic energy than a steady force-displacement curve whose force is a constant during a collision. Besides, the larger the slope of the force-displacement curve, the more energy is absorbed. In addition, the force-displacement relationship of the three-section metal turning tube under axial compression was studied and is found that with certain design parameters, the force-displacement relationship curve is almost in form of two equal gradients. At the same time, the tube's stroke effciency is up to 76.5%, which is more than 95% of the theoretical stroke efficiency (80%), proving that the three-section metal turning tube has a good deformability and energy absorption capacity.